Aplikasi QR Code untuk Keragaman Hayati di Puncak Labuang - Fryonanda, Harfebi; Vadreas, Andrew Kurniawan; A'yunin, Qurhata; Pratama, Fikri Wilya; Jonitra, Farhan (Penerbit Widina, Widina Media Utama, 2024)
Puncak Labuang Agrotourism in Limau Manih, Pauh District, Padang, is an educational tourism destination with great potential, especially in terms of natural beauty and biodiversity. However, the lack of accessible information for visitors limits understanding and awareness of the importance of environmental conservation. This program introduces a QR Code-based application to make it easier for visitors to access information about plant species and local ecosystems. The development method uses a prototyping approach, including needs analysis, prototype design, testing, and application implementation. QR Codes are placed on important plants, directing users to detailed information integrated with an interactive map. The program results show increased visitor awareness of conservation, community participation in information management, and promotion of the area as an environmentally friendly destination that contributes to the local economy. This innovation is expected to become a model for technology-based tourism management in the future.ABSTRAKAgrowisata Puncak Labuang di Limau Manih, Kecamatan Pauh, Padang, merupakan destinasi wisata edukatif dengan potensi besar, terutama dari keindahan alam dan keanekaragaman hayati. Namun, kurangnya informasi yang dapat diakses pengunjung membatasi pemahaman dan kesadaran akan pentingnya pelestarian lingkungan. Program ini memperkenalkan aplikasi berbasis QR Code untuk memudahkan pengunjung mengakses informasi tentang spesies tanaman dan ekosistem lokal. Metode pengembangan menggunakan pendekatan prototyping, meliputi analisis kebutuhan, desain prototipe, pengujian, dan implementasi aplikasi. QR Code dipasang pada tanaman penting, mengarahkan pengguna ke informasi terperinci yang terintegrasi dengan peta interaktif. Hasil program menunjukkan peningkatan kesadaran pengunjung terhadap konservasi, partisipasi masyarakat dalam pengelolaan informasi, serta promosi kawasan sebagai destinasi ramah lingkungan yang berkontribusi pada ekonomi lokal. Inovasi ini diharapkan menjadi model bagi pengelolaan wisata berbasis teknologi di masa depan.